The incidence of the root-knot nematode Meloidogyne incognita and Meloidogyne hapla in Slovenia - Saša ŠIRCA; Gregor UREK; Gerrit KARSSEN (Acta Agriculturae Slovenica)
The root knot nematode Meloidogyne incognita (Kofoid and White) Chitwood, 1949 is one of the most harmful and most ubiquitous species in the genus Meloidogyne. It was detected very often in the greenhouses of northern Europe, but in the open field it is restricted to the southern parts of Europe.  While this species has been recorded in almost all parts of the world and also in some parts of the former Yugoslavia, there is no data about its presence in Slovenia. M. incognita is able to parasitize about 700 plant hosts and varieties including the majority of economically important crops. In the late summer of 2002, nematodes of M. incognita were isolated from the roots of hot pepper plants, Capsicum annum L., from the greenhouse situated in Portorož at the Adriatic Coast, Slovenia. The nematode was morphologically identified as M. incognita and confirmed by isozyme gel electrophoresis (PhastSystem, Pharmacia). To our knowledge, this is the first report of M. incognita in Slovenia. Beside this finding, M. hapla was also found for the first time in the open field in Slovenia; until now it has been detected on different host plants grown only in greenhouses. In October 2002, M. hapla was isolated from galls of the sweet pepper grown in the open field in Ljubljana situated in the central part of Slovenia.